Optimalisasi Penerapan Model Discovery Learning untuk Meningkatkan Motivasi dan Hasil Belajar IPA Siswa SD Negeri 37 Cakranegara Pasca Pandemi Covid-19 - I Dewa Gede Lawa (Universitas Pendidikan Mandalika, 2022)
This study aims to describe the application of the discovery learning model to improve students' motivation and science learning outcomes after the Covid-19 pandemic at SDN 37 Cakranegara. This research method uses classroom action research which is carried out in two cycles, each cycle includes planning, implementation, observation and reflection activities. The research subjects were students of class V.b totaling 13 people. The research instruments used were observation sheets, documentation, and tests. The data analysis technique is descriptive analysis. The results showed that the teacher's observations in cycle II obtained an average score (4.52) and the results of student observations reached an average score (4.18). Meanwhile, students' science learning outcomes reached an average value (82.58), meaning that the success indicators (> 4.0) and science learning outcomes (> 75.00) had been exceeded. Because the indicators of success have been proven, the research was declared successful and was discontinued in cycle II. So the results of this study can be concluded that optimizing the application of the discovery learning model has been able to increase students' motivation and science learning outcomes after the Covid-19 pandemic at SDN 37 Cakranegara.